Earnings quality of Malaysian IPO firms: the effect of share moratorium provision and institutional ownership - Kalgo, Sani Hussaini; Amin, Bany Ariffin; Nahar, Hairul Suhaimi; Turmin, Siti Zaidah (Elsevier, 2016)
The paper focuses on earnings quality (EQ) of Malaysian Initial Public Offering (IPO) firms and examines the effect of share moratorium regulation and institutional ownership on IPO firms’ EQ behavior. Analyzing both real and accrual earnings management (EM) to measure EQ of 220 sample IPO firms over the period from 2002 to 2009, the results indicate that Malaysian IPO firms engage in both real and accrual discretionary EM. Both EQ measures are also observed to be similar between firms with and without share moratorium provision, evidencing the support towards Malaysia's public policy guideline of subjecting all IPO firms to share moratorium regulations as a commitment device to reduce information asymmetry and adverse selection problem between the strategic owners and new investors. The multivariate results further indicate the effective monitoring of institutional shareholders over investee firms’ EQ. The overall results collectively suggest the need for investors to examine investee firms’ real activity discretionary behavior in their investment decisions while regulators should device means of constraining it.